2022
DOI: 10.54083/resbio/4.3.2022/113-118
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Correlation and Path Coefficient Analysis for Yield and Associated Traits in Bread Wheat (Triticum aestivum L.)

Abstract: Wheat (Triticum aestivum L.) is the world's most important cereal grain which contains carbohydrate, protein, fat, minerals and significant amounts of vitamins. A study was conducted in Augmented Block Design with 105 genotypes of bread wheat with four checks (HD-2967, DBW-222, DBW-107, and HD-2733) for estimation of means, range, correlations and path-coefficient. A wide range of variations were observed for different characters under study. The genotype , , , produced highest grain yield plant -1 followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
4
4
0
Order By: Relevance
“…Since the direct effect were negative, so the direct selection for these traits to improve yield will be undesirable. Similar results were in accordance with findings of Singh et al [20]; Zu et al [16]; Kumar et al [21]; Ayer et al [22]; Nagar et al [18]. Number of grains per spike showed positive indirect effect via plant height, biological yield per plant.…”
Section: Direct and Indirect Effectssupporting
confidence: 92%
See 1 more Smart Citation
“…Since the direct effect were negative, so the direct selection for these traits to improve yield will be undesirable. Similar results were in accordance with findings of Singh et al [20]; Zu et al [16]; Kumar et al [21]; Ayer et al [22]; Nagar et al [18]. Number of grains per spike showed positive indirect effect via plant height, biological yield per plant.…”
Section: Direct and Indirect Effectssupporting
confidence: 92%
“…The results indicate that several factors, plant height, biological yield per plant, number of grains per spike, days to maturity and 1000grain weight had positive direct effect on grain yield. Similar findings reported by Sharma et al [14]; Santhoshini et al [15]; Singh et al [20]. Consequently, focusing and selecting these specific traits would prove beneficial in effectively enhancing the overall productivity of bread wheat.…”
Section: Direct and Indirect Effectssupporting
confidence: 86%
“…The plant's biological yield (0.30) had the largest positive direct impact on grain yield per plant, followed by the weight of 1000 grains (0.16), harvest index (0.13), tillers per plant (0.10), grains per spike (0.08), days to maturity (0.02), and peduncle length (0.01). Singh and Sharma, [16]; Khan et al, [4]; Anwar et al, [7]; Kumar et al, [13]; Dutamo et al, [14]; Singh et al, [11]; Sharma et al, [6] also reported the similar findings. The direct effects of the remaining characters were determined to be insignificant enough to warrant consideration.…”
Section: Resultsmentioning
confidence: 54%
“…In the current investigation, harvest index, 1000-grain weight, and biological yield per plant were found to be significant direct yield contributing variables through correlation and path coefficient analysis. The findings of Sharma et al [5], Anwar et al [7], Singh et al [11], Singh et al [15], Potdukhe et al [12], Kumar et al [13], Dutamo et al [14], and Singh et al [16] are comparable to these results. The aforementioned characters were worthy of consideration when formulating a selection strategy intended to produce high-yielding wheat varieties [17][18][19].…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation